Sustainability of Developed Self-Regulation by Means of Formative Assessment Among Young Adolescents: A Longitudinal Study - Beekman, Kelly; Joosten-Ten Brinke, Desirée; Boshuizen, Els (Frontiers in Education, 2021)
Abstract The present study examined the long-term impact of a formative assessment intervention in primary education on the development of students’ levels of self-regulation, motivation, and self-efficacy after their transition to secondary education. Participants in the study included 695 Dutch sixth graders from 17 schools. A longitudinal design with measurements on three time points was adopted. The first part of the study, consisting of a pretest, the intervention, and posttest, was conducted during the students’ last seven months in primary education using two experimental conditions, with peer- and self-assessment, and a control condition. A follow-up took place 10 weeks later, after the summer break and at the commencement of the participants’ secondary education. Longitudinal multilevel analyses showed that the development of self-regulation and motivation is significantly positively associated with the formative self- and peer-assessment interventions and continues after the transition to secondary education. Results are discussed with regard to theoretical and practical consequences.